SYNERGY BETWEEN CLIMATE POLICY AND THE LOCAL ECONOMY: THE ROLE OF RESILIENCE TO HYDROMETEOROLOGICAL DISASTERS IN THE CITY OF SUNGAI PENUH - Kharisma Putri, Alvinia; Adi Putri, Indah; Hendrik, Doni (Qawwam : The Leader's Writing, 2025)
Climate change has increased the frequency and intensity of hydrometeorological disasters in various regions of Indonesia, including Sungai Penuh City, Jambi Province. This city faces a high risk of flooding, landslides, and changes in rainfall patterns that directly impact the local economy, particularly agriculture and trade. This study aims to analyze the synergy between climate policy and local economic development through strengthening resilience to hydrometeorological disasters. The method used is a qualitative approach with descriptive analysis based on literature studies and secondary data. The results of the study show that the success of climate policy is highly dependent on cross-sector collaboration between local governments, businesses, and communities. Disaster resilience plays an important role as a link between climate adaptation and local economic stability. The main recommendation of this study is the need to integrate climate policy into regional development plans by strengthening early warning systems, adaptive spatial planning, and community-based green economy.